BHBA Influences Bovine Hepatic Lipid Metabolism via AMPK Signaling Pathway. Issue 6 (10th April 2015) - Deng, Qinghua; Liu, Guowen; Liu, Lei; Zhang, Yuming; Yin, Liheng; Shi, Xiaoxia; Wang, Jianguo; Yuan, Xue; Sun, Guoquan; Li, Yu; Yang, Wei; Guo, Lihui; et al.
ABSTRACT: β‐hydroxybutyric acid (BHBA), an important metabolite in β‐oxidation, is involved in the development of ketosis in dairy cows. It is known that AMP‐activated protein kinase (AMPK) signaling pathway plays an important role in the regulation of lipid metabolism in hepatocytes. In the present study, bovine hepatocytes were treated with BHBA at variable concontrations and Compound C (Cpd C, an AMPK inhibitor) to investigate the effects of BHBA on the AMPK signaling pathway. The results showed that when the concentration of BHBA reached 1.2 mM, the AMPK signaling pathway was activated and the expression of sterol regulatory element binding protein‐1c (SREBP‐1c) as well as its target genes were significantly decreased. And these decreases were blocked by Cpd C. The binding activity and nucleus translocation of SREBP‐1c showed a similar trend. The expression of peroxisome proliferator activated receptor‐α (PPARα), carbohydrates response element binding protein (ChREBP) and their target genes were significantly increased while they were negatively suppressed by the Cpd C. The content of triglyceride (TG) had no obviously change in the BHBA and Cpd C‐treated groups. These results indicate that BHBA can activate AMPK signaling pathway and regulate lipid synthesis and lipid oxidation genes of AMPK but showed no effect on TG in bovine hepatocytes. J. Cell. Biochem. 116: 1070–1079, 2015. © 2015 Wiley Periodicals, Inc.